Biofilm formation in total hip arthroplasty: prevention and treatment. Issue 83 (23rd August 2016) - García-Gareta, Elena; Davidson, Christopher; Levin, Alexandra; Coathup, Melanie J.; Blunn, Gordon W.
Abstract : This review assesses the current knowledge on treatments, pathogenesis and the prevention of infections associated with orthopaedic implants, with a focus on total hip arthroplasty. Abstract : Biomaterials science is a very active area of research, which has allowed the successful use of implants in the orthopaedic field for over a century. However, implant infection remains a clinical concern as it is associated with extensive patient morbidity and a high economic burden, which is predicted to increase due to an ageing population. Bacteria are able to adhere, colonise and develop into biofilms on the surface of biomaterials making associated infections physiologically different to other post-surgical infections. Unfortunately, biofilms exert increased protection from the host immune system and an increased resistance to antibiotic therapy in comparison to their planktonic counterparts. The aim of this review is to assess the current knowledge on treatments, pathogenesis and the prevention of infections associated with orthopaedic implants, with a focus on total hip arthroplasty.